Sexual cannibalism increases male material investment in offspring: quantifying terminal reproductive effort in a praying mantis - Brown, William D. (Proc Biol Sci, 2016)
Models of the evolution of sexual cannibalism argue that males may offset the cost of cannibalism if components of the male body are directly allocated to the eggs that they fertilize. We tested this idea in the praying mantid Tenodera sinensis. Males and females were fed differently radiolabelled crickets and allowed to mate. Half of the pairs progressed to sexual cannibalism and we prevented cannibalism in the other half. We assess the relative allocation of both male-derived somatic materials and ejaculate materials into the eggs and soma of the female. Our results show that male somatic investment contributes to production of offspring. The eggs and reproductive tissues of cannibalistic females contained significantly more male-derived amino acids than those of non-cannibalistic females, and there was an increase in the number of eggs produced subsequent to sexual cannibalism. Sexual cannibalism thus increases male material investment in offspring. We also show that males provide substantial investment via the ejaculate, with males passing about 25% of their radiolabelled amino acids to females via the ejaculate even in the absence of cannibalism.